A Comparative Study on the Aggregation and Thermodynamic Properties of Anionic Sodium Dodecylsulphate and Cationic Cetyltrimethylammonium Bromide in Aqueous Medium: Effect of the Co‐solvent N‐Methylacetamide. Issue 1 (16th October 2015) - Chauhan, Suvarcha; Kumar, Kuldeep; Rana, Dilbag S.; Kumar, Rajender; Chauhan, Mohinder S.
Abstract: The effect of co‐solvent N ‐methylacetamide (NMA) (0.035, 0.046, 0.127, and 0.258 mol kg −1 ) on the micellization behaviour of anionic surfactant sodium dodecylsulphate (SDS) (3.21–10.35 mmol kg −1 ) and cationic surfactant cetyltrimethylammonium bromide (CTAB) (0.19–3.72 mmol kg −1 ) in aqueous solution was explored by employing conductivity measurements at different temperatures (298.15–313.15 K). The critical micelle concentration (CMC) values for SDS and CTAB in aqueous solutions of NMA were determined from the conductivity versus surfactant concentration plots. The variations in the CMC values of SDS with NMA concentration are in striking contrast to those observed in the case of CTAB. The various relevant thermodynamic parameters of micellization, viz. standard enthalpy change, Δ H m o, standard entropy change, Δ S m o, and standard Gibbs free energy change, Δ G m o, were determined using the temperature variation of the CMC values and counterion binding. The results not only relate these thermodynamic parameters to the consequences of intermolecular interactions but are also able to differentiate between SDS–water–NMA and CTAB–water–NMA systems in terms of contributions from head groups as well as alkyl chains of surfactants.